Diskusi Kebangsaan: Aktualisasi Peran Pemuda Dalam Mewujudkan Demokrasi - Muhammad Iqbal (Universitas Maritim AMNI Semarang, 2023)
Youth are an important part of society and have a very strategic role in shaping the future of the country. However, youth are often less involved in the country's political and economic affairs, this creates problems that impact the quality of life of the community. Policies taken by the government often do not have a positive impact on youth, and do not prioritize their interests. This causes youth to not understand the importance of their role in shaping the future of the country and solving the problems they face. This activity aims to provide education to youth about democracy that is healthy, peaceful and in accordance with the time. Therefore, it is important to seek the role of youth in realizing democracy and a stable political economy, so that youth can play a more active role and have a positive impact on society.